1988
DOI: 10.1128/iai.56.9.2400-2406.1988
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Plasmodium chabaudi in B10 mice: influence of the H-2 complex and testosterone

Abstract: Resistance to Plasmodium chabaudi has been examined in different inbred mouse strains bearing identical H-2 haplotypes on different genetic backgrounds as well as in H-2-congenic mouse strains on B10 background. Resistance is expressed in terms of percent survival after a challenge with 106 P. chabaudi-infected erythrocytes. We can show that murine resistance to P. chabaudi is under complex polygenic control involving a non-H-2 gene(s) as well as genes in both I-A and I-E subregions of the H-2 complex. Our dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(32 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…Te even increases the susceptibility towards arthropod ectoparasites such as ticks (Ali & Sweatman 1966). Recently, a crucial role of Te has also been documented in the outcome of murine malaria caused by Plasmodium chabaudi (Wunderlich et al 1988) and P . berghei (Kamis & Ibrahim 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Te even increases the susceptibility towards arthropod ectoparasites such as ticks (Ali & Sweatman 1966). Recently, a crucial role of Te has also been documented in the outcome of murine malaria caused by Plasmodium chabaudi (Wunderlich et al 1988) and P . berghei (Kamis & Ibrahim 1989).…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous findings showing that Te exerts suppressive activities on diverse humoral and cellular immune reactions both in oiuo and in uifro (Kotani, Nawa & Fujii 1974, Morton et al 1981, Weinstein & Berkovich 1981, Dunkel et al 1985, Rife et al 1990). Thus, it has been suggested that Te prevents self-healing of P. chabaudi infections by suppressing the development of protective immunity (Wunderlich et al 1988). Alternatively, however, it is also possible that protective immune mechanisms are mounted even under Tetreatment, but these do not take effect for unknown reasons.…”
Section: Introductionmentioning
confidence: 99%
“…TESTOSTERONE HAS A suppressive effect on immune responses of vertebrates (for reviews, see refs [1][2][3][4] and increases susceptibility toward numerous infectious diseases (for reviews, see refs 5, 6). In the experimental malaria Plasmodium chabaudi, for example, the suppressive effect of testosterone manifests itself as a host conversion from resistance to susceptibility: normally self-healing infections result in a fatal outcome (7,8). Concomitantly, testosterone induces a change in T cells from a resistance-promoting phenotype to a susceptibility-mediating phenotype, thus enabling the T cells to mediate the suppressive effect of testosterone (9).…”
mentioning
confidence: 99%
“…The non-clonal line of P. chabaudi [40], resembles P. chabaudi AS in terms of restriction fragment length polymorphism as well as dihydrofolate reductase and cysteine protease sequence identities [41]. Moreover, the used line of P. chabaudi is self-healing as the AS clone, which is under control of genes of the H-2 complex and the non-H-2 background as well as sex and sex hormones of the infected mouse strain [42]. The Balb/c mice were infected with 10 6 P. chabaudiinfected erythrocytes.…”
Section: Protective Vaccinationmentioning
confidence: 99%